Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
Hello,
Step-by-step explanation:
[tex]x(a-b)=a(b-x)\\\\x(a-b)=ab-ax\\\\x(a-b)+ax=ab\\\\x(a-b+a)=ab\\\\x(2a-b)=ab\\\\\\x=\dfrac{ab}{2a-b} \ if\ 2a-b\neq 0[/tex]
Answer:
[tex]{ \sf{x(a - b) = a(b - x)}} [/tex]
Open the brackets:
[tex]{ \sf{ax - bx = ab - ax}} \\ { \sf{2ax - bx= ab }}[/tex]
Factorise out x:
[tex]{ \sf{x(2a - b) = ab}} \\ { \sf{x(2a - b) = ab}} \\ { \sf{x = \frac{ab}{2a - b} }}[/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.